UPAYA KEPALA SEKOLAH DALAM MENINGKATKAN MUTU KEGIATAN BELAJAR MENGAJAR DI ATABA QUR’AN CENTER KECAMATAN JATISARI BEKASI TAHUN PELAJARAN 2023/2024 - Syarif Hidayatulloh; Dewi Yanti; Mansur (UNISAN JURNAL, 2024)
This research aims to describe the school principal’s efforts to improve the quality of teaching and learning activities at the Ataba Qur’an center Bekasi which consists of: 1. Madarasah principal’s efforts to improve the quality of teaching and learning activities, 2. Supporting and inhibiting factors in improving the quality of teaching and learning activities. This research uses descriptive qualitative research methods. The informants in this research were the principal, curriculum representatives and teachers. The key informant in this research is the school principal because he is directly involved in education quality management at the Ataba Qur’an center, Bekasi. Data collection techniques use observation, interviews and documentation studies. Test the validity of the data by increasing diligence in research and using reference materials.The results of the research show that the Principal’s efforts to improve the quality of teaching and learning activities at the Ataba Qur’an center Bekasi are: 1) preparing professional educators, either through coaching, discussions and meetings, including teacher training, workshops, training, 2) Conditioning a learning environment that is safe, comfortable and stimulating in learning, making programs according to students’ needs, providing learning motivation both giving rewards to teachers and students, and 3) efforts to achieve academic and non-academic achievements.